Три круга войны: повесть / Михаил Колосов - Колосов Михаил Макарович (Подвиг, 1988)
Экземпляры: ф. 6 (20211202) / Инвентарный номер: 17464 / Цена: 1.90 / Авт.знак: К61 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6